Comparison of pharmacokinetic profile of levodopa throughout the day between levodopa/carbidopa/entacapone and levodopa/carbidopa when administered four or five times daily - Kuoppamäki, Mikko; Korpela, Kirsi; Marttila, Reijo; Kaasinen, Valtteri; Hartikainen, Päivi; Lyytinen, Jukka; Kaakkola, Seppo; Hänninen, Jutta; Löyttyniemi, Eliisa; Kailajärvi, Marita; Ruokoniemi, Päivi; Ellmén, Juha (European journal of clinical pharmacology, 2009)
Objectives To compare plasma levodopa concentrations after repeated doses of levodopa/carbidopa/entacapone (LCE) and levodopa/carbidopa (LC). Methods Open-label, randomized, two-period, active-controlled, cross-over study with four dosing regimens: groups I and II (healthy volunteers and Parkinson's disease patients) received levodopa 100 mg or 150 mg four times daily, respectively, and groups III and IV (healthy volunteers) received the same strengths of levodopa five times daily. Pharmacokinetic (PK) parameters determined for levodopa included Cmin, Cmax, Cmax - Cmin, AUC, t₁/₂, and tmax. Results In healthy volunteers and PD patients, mean trough levels (Cmin), Cmax, and AUC of levodopa were, in general, significantly higher during LCE compared to LC administration. Compared to Cmin, Cmax, and AUC, differences between the treatments in variability of levodopa concentrations (Cmax - Cmin) were less consistent. Conclusions The present results on the differences in levodopa PK between LCE and LC provide a basis to evaluate the relationship of levodopa PK and the induction of motor complications in an on-going study in early Parkinson's disease using similar dosing regimens.